PENGEMBANGAN KOMIK DIGITAL SAHABAT BELAJAR AKHLAK “SABELAK” SEBAGAI MEDIA PEMBELAJARAN PAI DI SD KELAS II - Nisa Khoerunajah; Farah Nur Fadhilah; Aning Novita; Ani Nur Aeni (FASHLUNA, 2022)
This research was conducted to determine the effect of digital comic learning media in learning Islamic Religious Education in grade II Elementary School. This research method is Design & Development (D&D). The media developed is in the form of digital comics. Based on the results of the study, it was found that before using comics, grade II students were still unfamiliar with the term good morals, while after using comics grade II students could know 4 to 5 kinds of good morals. Thus, it is proven that the use of digital comics as a learning medium is able to increase students' knowledge of good morals.